2021
DOI: 10.3390/app11146568
|View full text |Cite
|
Sign up to set email alerts
|

Sheep’s and Goat’s Frozen Yoghurts Produced with Ultrafiltrated Whey Concentrates

Abstract: The objective of this work was the use of goat and sheep liquid whey concentrates (LWCs) produced by ultrafiltration (UF) for the manufacturing of frozen yoghurts. In a first step, natural yoghurts using only goat’s and sheep’s LWCs as raw material were obtained. One day after production, these yoghurts were used to produce frozen yoghurts with different concentrations of added inulin. The physicochemical characteristics of ewe’s and goat’s yoghurts were significantly different regarding dry matter, protein, f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…The overrun values ( Table 4 ) are higher in sheep’s ice creams when compared to goat’s ice creams; however, in all cases, overrun values can be considered low when compared to data referred by other authors [ 17 ]. Regarding the meltdown rate, S-Yoghurt and S-Probiotics presented lower values, with the latter presenting the higher resistance to melt.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The overrun values ( Table 4 ) are higher in sheep’s ice creams when compared to goat’s ice creams; however, in all cases, overrun values can be considered low when compared to data referred by other authors [ 17 ]. Regarding the meltdown rate, S-Yoghurt and S-Probiotics presented lower values, with the latter presenting the higher resistance to melt.…”
Section: Resultsmentioning
confidence: 71%
“…A possible solution can be the utilization of liquid SCW concentrated by ultrafiltration (UF) or nanofiltration (NF) as the main ingredient to produce fermented drinks or other dairy products, as is the case of ice cream. We recently evaluated the performance of sheep’s and goat’s whey in the production of frozen yoghurts [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lower levels of protein in goat kefir was the cause for their liquid nature. Marnotes et al [ 23 ] also observed that sheep yogurts before freezing were solid, and goat yogurts were viscous liquids due to differences in protein concentrations of the LWCs used as raw materials.…”
Section: Discussionmentioning
confidence: 99%
“…The results of cost–benefit and sensitivity analyses show that an integrated process of ultrafiltration/nanofiltration (UF/NF) is economically viable in small/medium cheese producers [ 20 ]. Sheep dairy products, other than cheese, are also being developed and are looked at as an opportunity to valorize peripheral rural areas through the transformation of dairy products into competitive value-added commodities [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of cost-benefit analysis and sensitivity analysis show that an integrated process of ultrafiltration/nanofiltration (UF/NF) is economically viable in small/medium sized cheese dairies [16]. Sheep's dairy products other than cheese are also being developed and are looked at as an opportunity to valorize peripheral rural areas through the transformation of dairy products into competitive value-added commodities [17][18][19]. Concomitantly, increasing awareness on health has increased demand for healthy food which is confirmed by raising market sales of functional foods.…”
Section: Introductionmentioning
confidence: 99%